2022
DOI: 10.1007/s10549-021-06484-1
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation/fibrinolysis and circulating tumor cells in patients with advanced breast cancer

Abstract: Purpose To evaluate the relationship between circulating tumor cells (CTCs) and standard coagulation tests in both a discovery and a validation cohort of patients with advanced breast cancer. Methods In a retrospective (n = 77) and a prospective (n = 92) study of patients with progressive advanced breast cancer, CTC count, platelet number, fibrinogen level, D-dimers, prothrombin time, and activated partial thromboplastin time were measured. The association… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Histologically, fibrocellular intimal proliferation of small pulmonary vessels can be seen. This eventually can lead to stenosis and occlusion of the pulmonary vessels through the tumor cells themselves and through local release of tissue factors, leading to thrombosis due to activation of the coagulation system [5,11,12]. CTCs and CTC clusters are associated with severe outcome with rapid progression and early death in patients with metastatic breast cancer [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, fibrocellular intimal proliferation of small pulmonary vessels can be seen. This eventually can lead to stenosis and occlusion of the pulmonary vessels through the tumor cells themselves and through local release of tissue factors, leading to thrombosis due to activation of the coagulation system [5,11,12]. CTCs and CTC clusters are associated with severe outcome with rapid progression and early death in patients with metastatic breast cancer [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gkountela et al [14] demonstrated that the ability of CTCs to form clusters has been linked to increased metastatic potential. Furthermore, there is an association between CTCs, circulating tumor microemboli, and intravascular coagulation activation in progressive breast cancer [9, 12]. In this patient, detection of CTCs and CTC clusters was not performed, but retrospectively, it might have been a relevant additional diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Recently, Patel et al found a more than 10% incidence rate of prolonged APTT in patients treated with immune checkpoint inhibitors (ICIs). 32 , 33 Interestingly, lengthened APTT was also a poor prognostic factor for overall survival (OS) in patients with NSCLC, 34 gallbladder cancer, 35 multiple myeloma, 36 gastric cancer, 37 breast cancer, 38 and even COVID-1939. Importantly, we are the first to report that APTT is a key biomarker for predicting HPD triggered by ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TME high group showed a negative correlation with the complement and coagulation cascades, while the TME low group displayed a negative association with the p53 signaling pathway (Supp Fig 2). Abnormal coagulation is a pathology recently found in different cancers ( Maruyama et al, 2022 ), which is related to the tumor thrombosis ( Dirix et al, 2022 ; Sun et al, 2022 ). Our study may propose a new function of GPCR in the pathology of abnormal coagulation, which deserves further experiments.…”
Section: Discussionmentioning
confidence: 99%